2011
DOI: 10.4236/jbnb.2011.21012
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Oligoglycine Layers on Mica Surface

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…4c,e reveal that tectomers adapt to the nanotube curved surface. The successful coating suggests that the oligoglycine assembly can be promoted on the MWCNT-COOH surface in similar fashion to the tectomer assembly reported on mica 48 or viruses. 52,53 Electrostatic interactions between the protonated amino terminal groups of oligoglycine and the negative charges of the carboxylic acid groups of the MWCNT-COOH (point of zero charge pH PZC 3.1) 65 account for the hybrid formation in water.…”
Section: Cnt/tectomer Hybridssupporting
confidence: 56%
See 2 more Smart Citations
“…4c,e reveal that tectomers adapt to the nanotube curved surface. The successful coating suggests that the oligoglycine assembly can be promoted on the MWCNT-COOH surface in similar fashion to the tectomer assembly reported on mica 48 or viruses. 52,53 Electrostatic interactions between the protonated amino terminal groups of oligoglycine and the negative charges of the carboxylic acid groups of the MWCNT-COOH (point of zero charge pH PZC 3.1) 65 account for the hybrid formation in water.…”
Section: Cnt/tectomer Hybridssupporting
confidence: 56%
“…2e,f. AFM and theoretical studies of structural features of the assemblies formed by oligoglycines reported elsewhere, 48,50,52 show a thickness value of 4.5 nm for 4T tectomers.…”
Section: Tectomer Formation and Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…With a view to fine‐tuning the design and industrial applications, the two‐antennary species are particularly attractive . The main feature of these compounds is that they are capable of forming well‐organized supramolecular self‐assemblies (tectomers) in aqueous media and specific coatings on solid substrates . The innate reason for the self‐assembly is the possibility for the onset of highly cooperative arrangements of intra‐ and intermolecular hydrogen bonds known as polyglycine II (PGII) motifs .…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that a suitable mutual orientation of the CO and NH groups in the neighboring antennae is obligatory, thus allowing the formation of one full turn of the 3 1 ‐helix as a minimum and the onset of sterically stabilized hydrogen bonds (a molecular recognition type interaction). The latter may result in extra‐stable supramolecular entities in the solution bulk (tectomers), and also in well‐structured adsorption layers at suitably chosen solid substrates . For the two‐antennary oligoglycines, this might be a charged boundary (e.g., mica) where the initial driving force for the formation of the adsorption layer is the interaction of the NH 3 + groups at the end of the antennae with the charged plate; or a hydrophobic plate, at which the adsorption layer is formed owing to hydrophobic interactions with the alkyl chain.…”
Section: Introductionmentioning
confidence: 99%